2020
DOI: 10.5137/1019-5149.jtn.27893-20.4
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of mitochondrial dna microsatellite instability in malaysian patients with primary central nervous system tumors

Abstract: AIM:To determine the mitochondrial microsatellite instability (mtMSI) status in a series of Malaysian patients with brain tumors. Furthermore, we analyzed whether the mtMSI status is associated with the clinicopathological features of the patients. MATERIAL and METHODS:Forty fresh frozen tumor tissues along with blood samples of brain tumor patients were analyzed for mtMSI by PCR amplification of genomic DNAs, and the amplicons were directly sequenced in both directions using Sanger sequencing. RESULTS:Microsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 61 publications
(70 reference statements)
1
7
0
Order By: Relevance
“…Two different studies demonstrated the D310 detection in normal adjacent epithelial cells of breast [179] and gallbladder carcinomas [180], in conjunction with a mutation-carrying cancerous tissues. The D310 mtMSI was also observed in 12% of brain tumor patients [176], 34% in rectal carcinoma, and 38% in sigmoid or colorectal carcinoma [181].…”
Section: Mitochondrial Microsatellite Instability (Mtmsi)mentioning
confidence: 90%
See 1 more Smart Citation
“…Two different studies demonstrated the D310 detection in normal adjacent epithelial cells of breast [179] and gallbladder carcinomas [180], in conjunction with a mutation-carrying cancerous tissues. The D310 mtMSI was also observed in 12% of brain tumor patients [176], 34% in rectal carcinoma, and 38% in sigmoid or colorectal carcinoma [181].…”
Section: Mitochondrial Microsatellite Instability (Mtmsi)mentioning
confidence: 90%
“…However, responsible mechanisms involving mtMSI are not much known [174]. Among all, the most frequently reported mtMSI is located in the D-loop region [176]. The D310 site is a mutational hotspot in primary tumors and described as a highly polymorphic homopolymeric C stretch [177].…”
Section: Mitochondrial Microsatellite Instability (Mtmsi)mentioning
confidence: 99%
“…More recently, we detected mtMSI in 20% of a series of 40 primary brain tumours. We observed a total of 8 different alterations within 2 loci, D310 and D16184, of mtMSI markers [ 141 ].…”
Section: Other Cancersmentioning
confidence: 99%
“…These alterations substantially alter mitochondrial respiration capacity, other than stimulating a higher rate of oxidative stress and apoptosis ( 45 ). mtDNA mutations frequently occur within the hypervariable D-loop region, particularly in a homopolycytidine stretch or near the replication origins of the mtDNA H-strand ( 11 ). This crucial region possesses a triple-stranded DNA structure, which is severely liable to the persistent effect of oxidative insults, thus, possibly increasing the rate of mutations.…”
Section: Mtdna-cnmentioning
confidence: 99%
“…mtDNA is recognized to be highly unstable and liable to damage compared to the nuclear genome, due to the persistent exposure to oxidative attack coupled with deficient DNA repair machinery ( 11 ). As a result, mtDNA suffers from the formation of sequence alterations or depletion of mtDNA content, consequently leading to various disorders and cancer tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%